No, the Sky Is Not Falling: Evidence of Accounting Student Characteristics at FSA Schools, 1995–2000 - Nelson, Irvin T.; Vendrzyk, Valaria P.; Quirin, Jeffrey J.; Allen, Robert D. (Issues in accounting education, 2002)
This article presents the most recent results of an ongoing, longitudinal study of characteristics of accounting students conducted by the Federation of Schools of Accountancy (FSA). Surveys were administered to seniors and Mastera^€™s students at FSA member schools in the United States in 1995 and again in 2000. Data regarding student characteristics in 1995 and 2000 are presented. Specifically, the study contains evidence pertaining to student quality, future educational plans, career plans, plans for professional certification, extracurricular involvement, attitude toward the 150-hour requirement, and various demographic dimensions. The results of the survey do not coincide with those of other studies that have reported a decline in the quality of accounting students. On the contrary, our findings suggest that the quality of accounting students is not decreasing. Further research is necessary to more fully understand these contradictory findings and the direction and magnitude of any changes in student quality. Other findings of this study include a reversal in the gender mix of graduate students, with females now comprising the majority. More graduate students are pursuing their studies full-time. The average age of students is declining. More accounting students are interested in taking the Certified Public Accountant (CPA) exam and pursuing careers in public accounting, while interest in the Certified Management Accountant (CMA) exam and in pursuing careers in industry are declining. Both seniors and Master's students indicate a very high level of support for five or more years of college education for the CPA. Student involvement in internship programs has nearly doubled since 1995, while involvement in extracurricular organizations has dropped. These results are relevant to many currently debated topics in accounting education—including the effects of the implementation of the 150-hour rule in many states.